2009
DOI: 10.4103/1742-6413.55894
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of galectin-3, CK19, HBME1, and Ret oncoprotein in the diagnosis of thyroid neoplasms by fine needle aspiration biopsy

Abstract: Background:Fine needle aspiration biopsy (FNAB) is a common and excellent procedure for the evaluation of thyroid lesions that require surgical resection. At times, the FNAB diagnosis can be difficult, particularly of follicular-patterned lesions. Previous studies have shown that some immunohistochemical (IHC) markers may be helpful in establishing more accurate diagnosis. In this study, our goal was to evaluate four of the recently investigated markers in differentiating benign from malignant thyroid nodules … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 31 publications
(48 reference statements)
2
41
0
1
Order By: Relevance
“…Such markers are helpful in the identification of malignant tumors, particularly papillary carcinomas (46). Although their sensitivity reaches 0.85 to 0.93, their specificity varies from 0.43 to 0.71 at most (47). Mutations in specific genes (such as BRAF V600E and RAS) or gene rearrangements (such as RET/PTC and PAX8-PPARy) can also contribute to the identification of malignancy (48).…”
Section: Recommendation 12mentioning
confidence: 99%
“…Such markers are helpful in the identification of malignant tumors, particularly papillary carcinomas (46). Although their sensitivity reaches 0.85 to 0.93, their specificity varies from 0.43 to 0.71 at most (47). Mutations in specific genes (such as BRAF V600E and RAS) or gene rearrangements (such as RET/PTC and PAX8-PPARy) can also contribute to the identification of malignancy (48).…”
Section: Recommendation 12mentioning
confidence: 99%
“…According to the literature, the sensitivity of CK-19 for malignancy ranges from 85% to 92% [19,20]. A value of 100% has been reported regarding the positive expression rate of CK-19 for papillary carcinoma in cell block material [21].…”
Section: Discussionmentioning
confidence: 99%
“…10,11 Its utility in thyroid carcinomas has been documented in several studies, revealing strong and diffuse cytoplasmic staining in PTCs. [12][13][14][15][16][17] It is considered the most specific marker (96%) for PTC by some authors, and the most sensitive and specific marker by others, reportedly staining 96% of PTCs and only 7% of BTN cases. 12,13 Other studies have demonstrated that immunoreactivity for HBME-1 is an indication of thyroid malignancy, but not necessarily of papillary differentiation.…”
Section: Discussionmentioning
confidence: 99%